Self-tuning Position Control for the Linear Long-stroke, Compound Switched Reluctance Conveyance Machine - J. F. Pan; Weiyu Wang; Zhang Bo; Norbert Cheung; Li Qiu (Institute of Advanced Engineering and Science, 2017)
This paper proposes a long-stroke linear switched reluctance machine (LSRM) with a primary and a secondary translator for industrial conveyance applications. The secondary one can translate according to the primary one so that linear compound motions can be achieved. Considering the fact that either one translator imposes a time-variant, nonlinear disturbance onto the other, the self-tuning position controllers are implemented for the compound machine and experimental results demonstrate that the absolute steady-state error values can fall into 0.03 mm and 0.05 mm for the secondary and primary translator, respectively. A composite absolute precision of less than 0.6 mm can be achieved under the proposed control strategy.